(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Major bone fractures, including those of the pelvis, femur, and tibia, represent a significant challenge in trauma care due to their high prevalence, complexity, and risk of complications. These injuries are often associated with substantial morbidity, prolonged rehabilitation, and, in severe cases, permanent disability. Advances in surgical techniques, such as metal osteosynthesis (MOS) using plates, screws, and external fixation devices, have improved treatment outcomes. However, complications such as delayed union, nonunion, infection, and thromboembolic events remain critical barriers to optimal recovery.